The first step in solving the equation \( -3 = \frac{x}{4} + 2 \) for \( x \) is to subtract 2 from both sides.
So, the correct response is: Subtract 2 from both sides.
Responses
Subtract 2 from both sides.
Subtract 2 from both sides.
Multiply both sides by 2.
Multiply both sides by 2.
Add 2 to both sides.
Add 2 to both sides.
Divide both sides by 4.
9 answers
The first step in solving the equation \( -3 = \frac{x}{4} + 2 \) for \( x \) is to subtract 2 from both sides.
So, the correct response is: Subtract 2 from both sides.
To solve the equation \( 10z - 6 = 24 \) for \( z \), follow these steps:
Add 6 to both sides:
\[ 10z - 6 + 6 = 24 + 6 \] \[ 10z = 30 \]
Divide both sides by 10:
\[ z = \frac{30}{10} = 3 \]
Therefore, the solution for \( z \) is \( 3 \).
The correct response is: 3.
Jonny subtracts 8 from both sides of the equation \( 8 + 3n = 20 \) to isolate the term with \( n \). This is because he wants to simplify the equation by getting rid of the constant on the left side.
The correct response is: 8 is attached to 3n by subtraction.
If Samuel's first step is to add 7 to both sides of the equation, he is likely solving an equation where subtracting 7 from one side gives you a value.
Let's analyze the answer choices:
\( 2y - 7 = 15 \)
To isolate \( y \), you would add 7 to both sides:
\[ 2y - 7 + 7 = 15 + 7 \implies 2y = 22 \]
\( 2y - 15 = 7 \)
To isolate \( y \), you would add 15 to both sides:
\[ 2y - 15 + 15 = 7 + 15 \implies 2y = 22 \]
\( 2y + 7 = 15 \)
To isolate \( y \), you would subtract 7 from both sides, not add:
\[ 2y + 7 - 7 = 15 - 7 \implies 2y = 8 \]
\( 2y + 15 = 7 \)
To isolate \( y \), you would subtract 15 from both sides:
\[ 2y + 15 - 15 = 7 - 15 \implies 2y = -8 \]
The only equation for which the first step makes sense—adding 7 to both sides—is:
\( 2y - 7 = 15 \)
If Kelia's second step is to multiply both sides of an equation by 4, it suggests that in the first step she had an equation where a term involving \( x \) was divided by 4. This would imply that in the first step, she would have needed to eliminate a fraction by multiplying both sides by 4.
Let's analyze each option:
\( 6 + 4x = 1 \)
In the first step, there is no division by 4. Thus, multiplying both sides by 4 wouldn't make sense as a second step.
\( 6 + \frac{x}{4} = 1 \)
In this case, if her first step was to subtract 6 from both sides, the equation would look like:
\[ \frac{x}{4} = 1 - 6 \implies \frac{x}{4} = -5 \]
Then, multiplying both sides by 4 would lead to:
\[ x = -20 \]
This means this equation fits what Kelia is doing.
\( 4 + \frac{x}{6} = 1 \)
Similar to before, she would need to multiply by 6, not 4, to eliminate the fraction.
\( 4 + 6x = 1 \)
Again, the first step does not involve a division by 4, so this would not make sense for a second step of multiplying by 4.
From this analysis, the correct equation Kelia is solving, where her second step involves multiplying by 4, is:
\( 6 + \frac{x}{4} = 1 \).